The Use of Transition Curves in Airport Runway Rapid Exit Taxiways (RETs) - Donato Ciampa; Maurizio Diomedi; Pietro Vuono; Saverio Olita (Advances in Civil Engineering)
This paper describes a study result focused on the transition curves used in airport rapid exit taxiways (RETs). Such geometric elements are not currently made explicit by standards, and major international government agencies, such as the International Civil Aviation Organization and the Federal Aviation Administration, are limited to providing some layouts consisting of only constant curvature elements, although the aircrafts speed in RETs is variable. In addition to the clothoid that has unitary shape parameter “n” and the multiparameter clothoids (generalized Cornu spirals), the study analyzes the Bloss curve employment. Regarding the multiparameter clothoids, four schemes with shape parameter equal to 1.25, 1.50, 1.75, and 2.00 were considered, respectively. The proposed curves’ effectiveness was evaluated by analyzing the main geometric and kinematic variables trend, that is, curvature, transversal acceleration, lateral jerk, speed, travel time, longitudinal deceleration, and centrifugal force. To ensure the analysis effectiveness, the study layouts were designed from those used for runways codes 1-2 and 3-4 maintaining the main geometric elements dimensions unchanged (length of straight lines, radii of circular curves, exit angles, etc.). The kinematic variables values along the design RETs were calculated “point by point” by MATLAB software to take into account nonuniform motion regimen. The obtained results show that both the Bloss curve and the multiparameter clothoid having a shape factor equal to 2 are capable of better contribution in terms of safety and comfort. Implications in the airport construction field are related to the possibility of using lower deceleration values compared to current standards, that is, allowing higher exit speed for the same deceleration. This allows aircrafts to vacate the runway more quickly and, therefore, to increase runway capacity without taking expensive RETs repositioning.